2022
DOI: 10.3389/fsurg.2022.959533
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid leaks following intradural spinal surgery—Risk factors and clinical management

Abstract: BackgroundCerebrospinal fluid leakage (CSFL) following spinal durotomy can lead to severe sequelae. However, while several studies have investigated accidental spinal durotomies, the risk factors and influence of clinical management in planned durotomies remain unclear.MethodsWe performed a retrospective analysis of all patients who underwent planned intradural spinal surgery at our institution between 2010 and 2020. Depending on the occurrence of a CSFL, patients were dichotomized and compared with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
(35 reference statements)
0
5
2
Order By: Relevance
“…However, several studies could not verify this. 2,4,11,34,39 In comparison with other studies, we could not find any association between the development of CSFL and underlying pathology-tumor vs nontumor-and localization level of the durotomy in the spine. 4,6,39 Furthermore, Jesse et al reported a higher incidence of CSFL when the approach was in the cervicothoracic junction, explained by the higher movements in that area 6 ; however, none of the patients in this study operated for pathology in this region developed a CSFL.…”
Section: Duraplasty As a Risk Factor For The Development Of Postopera...contrasting
confidence: 99%
See 2 more Smart Citations
“…However, several studies could not verify this. 2,4,11,34,39 In comparison with other studies, we could not find any association between the development of CSFL and underlying pathology-tumor vs nontumor-and localization level of the durotomy in the spine. 4,6,39 Furthermore, Jesse et al reported a higher incidence of CSFL when the approach was in the cervicothoracic junction, explained by the higher movements in that area 6 ; however, none of the patients in this study operated for pathology in this region developed a CSFL.…”
Section: Duraplasty As a Risk Factor For The Development Of Postopera...contrasting
confidence: 99%
“…These findings support previous results that bed rest does not play a significant role in preventing CSFL. 5,6,9,11,12 Beyond that, our data did not show an association between early mobilization and the occurrence of other postoperative adverse events.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This brief period of drainage allowed for early mobilization and a shorter hospital stay; our average hospital length of stay was five days. [ 2 ] Despite the use of SD, we found no postoperative infections, and just one patient reported a nonpositional headache immediately postoperatively and was later found to have COVID pneumonia. Notably, no patients developed postoperative CSF leaks, and no revision procedures were warranted within the 30–90 postoperative window.…”
Section: Discussionmentioning
confidence: 88%
“…Another possible complication of spinal surgery is CSF leak. CSF leak following spinal durotomy appears to occur in about 5% of cases and appears to be associated with prior surgery at the index level and cervical vs thoracic location, but does not appear to depend on dural closure technique or other covariates [24,34,48,49,50]. CSF leak is associated with serious infections including meningitis and healing disorders with subsequent repeat surgery [50].…”
Section: Surgical Resection and Complicationsmentioning
confidence: 99%